A reconnaissance of the geomorphology and glacial history of the upper Gordon River Valley, Tasmania - Kiernan, K (Forestry Tasmania, 1995)
A reconnaissance of the land forms and Quaternary sediments of the uppermost Gordon River Valley and adjacent Guelph River Valley indicates that at least two and probably three glaciations are represented. The most striking landforms produced by glacial erosion of the King William Range appear to date from glaciations that predate those recorded during this survey. When the ice cover was most extensive, the Gordon Glacier was nourished partly by diffluent ice from the Derwent and Guelph Valleys, but during the late Last Glacial Stage the Gordon Glacier was nourished primarily by local sources. The glacial sediments as far as 11 km from the head of the Gordon Valley are weathered to only a moderate extent and appear much younger than the heavily weathered drifts that define the maximum glacier limits in almost all other Tasmanian valleys studied previously. This suggests that the tills identified to date in the Gordon Valley are not likely to represent the maximum down-valley extent of the Gordon Glacier.